The Therapist’s Experience of the (Non-) Establishment of Therapeutic Alliance in Couple Therapy - Creagh, Helen (Auckland University of Technology, 2020)
This dissertation concerns the therapist’s experience of the establishment, or non-establishment, of therapeutic alliance in couple therapy. There is strong evidence that the therapeutic alliance has a significant impact on the outcomes of couple therapy. Although there is a considerable literature on therapeutic alliance in individual therapies, far fewer endeavours have been made in the realm of couple research. Even though the workings of the alliance within a therapeutic triad attract attention in published research, results have been contradictory and confusing. There is very little research which involves the therapist as subject or makes use of qualitative methodologies to answer key questions. There remains a lack of clarity about the definition of therapeutic alliance in couple therapy and about the importance of imbalance in the therapeutic triad. This research investigates experiences of registered psychodynamic therapists in the (non-) establishment of therapeutic alliance with couples. The methodology used is Interpretative Phenomenological Analysis (IPA). Five personal interviews conducted with experienced couple psychotherapists provide the data. Key research findings include that therapists actively seek the establishment of an alliance with couples and that the formation of an alliance is not a given. Imbalance in therapeutic alliance is common to the endeavour of couple therapy, particularly at the outset. Using a combination of therapeutic process and stance, therapists aim to deliver containment, equity, and both emotional and experiential safety to their couple clients. Challenges to alliance formation with couples include client factors, therapist factors and process errors.
Keywords: IPA; Therapist's experience; Couple Therapy; Therapeutic Alliance